Fusion for profit how marketing and finance can work together to create value - Jagpal, Sharan, 1947-; Jagpal, Shireen (New York : Oxford University Press, 2008)
Jagpal covers in a comprehensive way how financial models can help firms make important decisions. Chapter topics range from how to compensate a sales force, to pricing and bundling strategy, to the measurement of advertising productivity. Case studies from a variety of industries illustrate each of Jagpal's points.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Marketing -- Management; Marketing -- Costs